2009
DOI: 10.4067/s0718-58392009000200020
|View full text |Cite
|
Sign up to set email alerts
|

Life, Seasonal Cycles, and Population Fluctuation of Hippodamia variegata (Goeze) (Coleoptera: Coccinellidae), in the Central Plain of La Araucanía Region, Chile

Abstract: This study was performed on an alfalfa crop located on the central plain of La Araucanía Region, Chile and in the Laboratorio de Entomología Aplicada de la Facultad de Ciencias Agropecuarias y Forestales at the Universidad de La Frontera. Certain aspects of the biology of Hippodamia variegata (Goeze) (Coleoptera: Coccinellidae) were determined, more specifically in relation to its life cycle, seasonality, and population fluctuation. It was established that this coccinellid requires 190.32 ± 10.2 degree-days to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
7
0
3
Order By: Relevance
“…Compared with other generalist predators common in alfalfa, prey consumption is greater for coccinellids (Grez et al, 2007;Sarmento et al, 2007) than N. punctipennis, including Eriopis connexa (Germar), Adalia bipunctata (L.), and Hippodamia variegata (Goeze) (Coleoptera: Coccinellidae) (Zaviezo et al, 2004(Zaviezo et al, , 2006. However, nabids in alfalfa have a very dynamic presence (Zaviezo et al, 2004;Rebolledo et al, 2009). Thus, even though consumption per capita of the nabid is not too high, it has important characteristics, like being the predator most frequent in alfalfa in the Metropolitan Region (Villarroel, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with other generalist predators common in alfalfa, prey consumption is greater for coccinellids (Grez et al, 2007;Sarmento et al, 2007) than N. punctipennis, including Eriopis connexa (Germar), Adalia bipunctata (L.), and Hippodamia variegata (Goeze) (Coleoptera: Coccinellidae) (Zaviezo et al, 2004(Zaviezo et al, , 2006. However, nabids in alfalfa have a very dynamic presence (Zaviezo et al, 2004;Rebolledo et al, 2009). Thus, even though consumption per capita of the nabid is not too high, it has important characteristics, like being the predator most frequent in alfalfa in the Metropolitan Region (Villarroel, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Summers (1976) and Wheeler (1977) observed that populations of lady beetles in an alfalfa field in California and New York were high in May and September. More recently, a noticeable increase in a H. variegata population in early autumn was reported by Rebolledo et al (2009) from Chile. As in the present study, Rakhshani et al (2009) reported the peak of H. variegata on July 21 in the province of Isfahan (Central region of Iran), and their study confirms our results about the higher level of H. variegata.…”
Section: Discussionmentioning
confidence: 99%
“…However, their presence in alfalfa is very dynamic (Zaviezo et al, 2004;Rebolledo et al, 2009). Although the nabid per capita consumption is not high, it is the most common predator in alfalfa in the Metropolitan Region throughout crop growth, reaching maximum density in the spring, from November through December (Romero et al, 2007).…”
Section: Aphid Densitymentioning
confidence: 99%